Pertimbangan Hukum Hakim Dalam Kasus Tindakan Pencurian Kendaraan Bermotor Yang Di Lakukan Oleh Anak - Alfons, Revalno; Titahelu, Juanrico Alfaromona Sumarezs; Taufik, Iqbal (Faculty of Law, Universitas Pattimura, 2024)
Introduction: one of the motor vehicle theft cases is the Ambon District Court decision No. No.12/PID.SUS-ANAK/2021/PN.AMB which states that Ammar Peisamal alias Ammar was convicted of